The Use of External Knowledge of Factoid QA - Hovy, E.H.; Hermjakob, U.; Lin, Chin-Yew (The 10th Text Retrieval Conference (TREC 2001), 2001)
This paper describes recent development in the Webclopedia QA system, focusing on the use of knowledge resources such as WordNet and a QA typology to improve the basic operations of candidate answer retrieval, ranking, and answer matching.